The Influence of the Work Environment and Work System on the Work Motivation of Business Actors at Cipadu Market, Tangerang City, Banten Province - Hendradewi, Savitri; Dewi, Triana Rosalina; Rianto, Rianto; Adriani, Hanni; Abduh, Mohammad Syaltut (At-Tadbir : jurnal ilmiah manajemen, 2024)
This research aims to determine the influence of the work environment and work system on the work motivation of entrepreneurs at Cipadu Market. This type of research is descriptive research with a quantitative approach using multiple regression analysis methods, which was carried out at Cipadu Market. The partial research results show that the work environment and work system have a significant influence on the work motivation of entrepreneurs at Cipadu Market. The work environment has a significant influence on the work motivation of entrepreneurs because it is related to factors such as emotional support, market facilities, the role of market leaders, the level of competition, as well as economic conditions and textile market trends which play a role in influencing their motivation. The work system has a significant influence on the work motivation of business actors because it involves important aspects such as funding sources, product promotion, management staff and business financial management. Suggestions for business actors in the Cipadu market: create a positive work culture, promote team collaborati